Design and Implementation of a Paralleled Discrete SiC MOSFET Half-Bridge Circuit with an Improved Symmetric Layout and Unique Laminated Busbar - Ataseven, Ismail; Sahin, Ilker; Ozturk, Salih Baris (MDPI AG, 2023)
Silicon carbide (SiC) metal oxide semiconductor field effect transistors (MOSFETs) have many advantages compared to silicon (Si) MOSFETs: low drain-source resistance, high thermal conductivity, low leakage current, and high switching frequency. As a result, Si MOSFETs are replaced with SiC MOSFETs in many industrial applications. However, there are still not as many SiC modules to customize for each application. To meet the high-power requirement for custom applications, paralleling discrete SiC MOSFETs is an essential solution. However, it comes with many technical challenges; inequality in current sharing, different switching losses, different transient characteristics, and so forth. In this paper, the detailed MATLAB®/Simulink® Simpscape model of the SiC MOSFET from the datasheet and the simulation of the half-bridge circuit are investigated. Furthermore, this paper proposes the implementation of the four-paralleled SiC MOSFET half-bridge circuit with an improved symmetric gate driver layout. Moreover, a unique laminated busbar connected directly to the printed circuit board (PCB) is proposed to increase current and thermal capacity and decrease parasitic effects. Finally, the experimental and simulation results are presented using a 650 V SiC MOSFET (CREE) double-pulse test (DPT) circuit. The voltage overshoot problems and applied solutions are also presented.
Keywords: Technology; symmetric gate driver layout; paralleled SiC MOSFETs; double-pulse test (DPT) circuit; half-bridge; paralleled SiC MOSFETs; symmetric gate driver layout; laminated busbar; voltage overshoot; laminated busbar; voltage overshoot; double-pulse test (DPT) circuit; half-bridge